2017
DOI: 10.1039/c6nr09795b
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of carbon nanotube degradation in primary cells by photothermal imaging

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…In particular, the measurement of the integrated intensity ratio between the D and G bands (A D /A G ) is a way to semi-quantify the degree of structural defects in the nanotube sample (Table 1). 33,34,36,45,55,56 Fig. 1b displays representative Raman spectra of p-MWCNT, 2 and 9 h pre-oxidized MWCNT samples showing the characteristic D and G bands at ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the measurement of the integrated intensity ratio between the D and G bands (A D /A G ) is a way to semi-quantify the degree of structural defects in the nanotube sample (Table 1). 33,34,36,45,55,56 Fig. 1b displays representative Raman spectra of p-MWCNT, 2 and 9 h pre-oxidized MWCNT samples showing the characteristic D and G bands at ca.…”
Section: Resultsmentioning
confidence: 99%
“…Their lysosomes, apart from displaying a pH of 4.5, contain a large variety of enzymes (acid-hydrolases and peroxidases) that are able to gradually digest CNTs. [27][28][29][30][31][32][33] Macrophages, 32 microglia, [33][34][35][36] neutrophils 37,38 and eosinophils 31 have all been confirmed to degrade CNTs in culture after different previous surface treatments. Paradoxically, phagocytes are more susceptible than other cells to CNT-toxicity, at least in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of the pathways leading to the removal of nanomaterials from the organism is of major importance for their final application and is a required issue for the clearance of use in clinical trials. Nanocomposites, firstly considered as structurally persistent, were shown to be degraded by oxidative enzymes, among others, peroxidases [54][55][56][57]. It was reported that single layer and few layers graphene is degraded by human MPO, which is released by neutrophils [58].…”
Section: Discussionmentioning
confidence: 99%
“…peroxidases) are able to catalyse the degradation of graphene oxide or carbon nanotubes in test tubes, in vitro and in vivo. [45][46][47][48] In addition, our very recent review carefully evaluated the role of the material properties including the number of layers, the lateral dimension and the C/O ratio in the degradation ability of each specific GBM (Fig. 4).…”
Section: Biodegradabilitymentioning
confidence: 99%